2018
DOI: 10.1615/plasmamed.2019028601
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Apoptosis by Cold Atmospheric Pressure Plasma for Oral Squamous Cell Carcinoma Cells

Abstract: Cold atmospheric pressure plasma (CAPP) techniques have developed rapidly durthat is comprised of reactive atoms, molecules, ions, and radicals. CAPP generates various types of highly reactive oxygen and nitrogen species at room temperature that play an important part in biological applications including cancer therapy. In recent years, CAPP has gained increasingly stood. The aim of this study is to investigate both the mechanism of CAPP on oral squamous cell carcinoma (OSCC) cells as well as plasma-induced ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 6 publications
1
8
0
Order By: Relevance
“…The selective toxicity of plasma treatment in vitro was demonstrated since human malignant keratinocytes (SCC) were significantly more sensitive to plasma treatment compared to human non-malignant (HaCaT) keratinocytes. This is in line with previous reports, showing a cytotoxic action and self-amplification of mitochondrial ROS production, following treatment in various human SCC cell lines, including FaDu, SNU1041, OSC19, SNU800, and HN9 [ 47 , 71 , 72 ]. Another study reported the involvement of catalytic iron in eliciting ferroptosis in plasma-treated human and mouse SCC lines, such as SAS, Ca9-22, HSC-2, HSC-3, HSC-4, Sa3, and Ho-1-u-1 [ 73 ].…”
Section: Discussionsupporting
confidence: 93%
“…The selective toxicity of plasma treatment in vitro was demonstrated since human malignant keratinocytes (SCC) were significantly more sensitive to plasma treatment compared to human non-malignant (HaCaT) keratinocytes. This is in line with previous reports, showing a cytotoxic action and self-amplification of mitochondrial ROS production, following treatment in various human SCC cell lines, including FaDu, SNU1041, OSC19, SNU800, and HN9 [ 47 , 71 , 72 ]. Another study reported the involvement of catalytic iron in eliciting ferroptosis in plasma-treated human and mouse SCC lines, such as SAS, Ca9-22, HSC-2, HSC-3, HSC-4, Sa3, and Ho-1-u-1 [ 73 ].…”
Section: Discussionsupporting
confidence: 93%
“…Kang et al showed the ROS-mediated inactivation of plasma-treated head and neck cancer cells could be rescued via the addition of antioxidants, which abolished plasma-mediated cytotoxicity through the reduction of apoptosis, levels of intracellular ROS, mitochondrial superoxide, and the loss of mitochondrial membrane potential (MMP) [32]. Besides the initiation of cell death mechanisms, ROS cause the general elevation of oxidative stress within cancer cells [26]. These ROS or secondary ROS may be able to alter cellular structures, such as DNA and RNA, and proteins could be damaged, potentially leading to autophagy and induction of the DNA-damage response.…”
Section: Hnscc and Oxidative Stressmentioning
confidence: 99%
“…Most of these experimental in vitro studies used the oral squamous cell carcinoma cell line SCC-15, as well as SCC-25, and highlighted their plasma-induced inactivation due to the reduction of cell growth, induction of apoptosis, and secondary DNA damage, especially through plasma-derived ROS [19,25,28,[34][35][36][37][38]. Other HNSCC cell lines were also tested, showing one or more of the tumor-toxic plasma-associated characteristics [6,19,22,24,[26][27][28][29][30][31][32][33]37]. In addition, HNSCC has been shown to be more prone to physical plasma treatment than non-malignant cells since the viability of the latter did not significantly decrease after plasma application.…”
Section: In Vitro and In Vivo Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Among these cancer types, the research presenting the beneficial effects of CAP on head and neck cancer only account for 3.28%, and research on the anti-cancer effect of CAP on OSCC is rare. Ramireddy et al reported that helium plasma jet treatment on OSCC causes apoptotic cell death due to the increase of oxidative stress in tumor cells [ 20 ]. In the case of Lee et al, it has been reported that the treatment of OSCC with nitrogen-based plasma jets induced apoptotic cell death, and they also proposed the increased intracellular level of reactive oxygen species (ROS) as a reason for this phenomenon [ 21 ].…”
Section: Introductionmentioning
confidence: 99%